2020
DOI: 10.1016/j.surfcoat.2020.125987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metal oxide micro/nanoparticles elaborated by plasma electrolytic oxidation of aluminium and zirconium alloys

Abstract: Highlights PEO process produces polycrystalline metal oxide particles (Al2O3 and ZrO2)  Particles exhibit a hollow spherical morphology with size between 0.01-10 µm  Morphology of the particles is correlated to the PEO "pancake" structure  A formation mechanism of particles during PEO is proposed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In general, the deposition of HOI coatings on light metals and their alloys improves their electrochemical stability under extreme conditions due to the delayed attack of aggressive species on the metal surface leading to the enhancement of the anticorrosion behavior. Among electrochemical analyses, potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) are the most commonly used techniques to scrutinize the corrosion behavior of HOI coatings on metallic materials [10,26,27]. PDP technique is used to understand the corrosion rate and susceptibility of materials to corrosion, whilst EIS technique together with equivalent circuit modelling describes corrosion mechanism providing relevant information regarding the roles of coating layers [19,28,29].…”
Section: Protective Performance: Polarization Behavior and Impedance Responsementioning
confidence: 99%
“…In general, the deposition of HOI coatings on light metals and their alloys improves their electrochemical stability under extreme conditions due to the delayed attack of aggressive species on the metal surface leading to the enhancement of the anticorrosion behavior. Among electrochemical analyses, potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) are the most commonly used techniques to scrutinize the corrosion behavior of HOI coatings on metallic materials [10,26,27]. PDP technique is used to understand the corrosion rate and susceptibility of materials to corrosion, whilst EIS technique together with equivalent circuit modelling describes corrosion mechanism providing relevant information regarding the roles of coating layers [19,28,29].…”
Section: Protective Performance: Polarization Behavior and Impedance Responsementioning
confidence: 99%
“…Some studies have shown that the ceramic particles are formed on the substrate surface and aggregated into the pancake form. [67,68] However, there are still a lot of gaps among these pancakes, causing the uniformity of the surface. As the micro-arc discharge reaction progresses, the melts are overflowed from the discharge micropores and accumulate around the micropores.…”
Section: Micropores and Microcracks In The Coatingsmentioning
confidence: 99%
“…In this case, the micropores could be free paths for diffusion of corrosive ions to the interface of substrate and coating, which is harmful to the corrosion resistance performance. Thus, the composite MAO coatings obtained in the electrolytes containing various nanoparticles have got more attention as they present compactness, microstructure modification, and/or sealing of pores, which leads to better corrosion protection 15‐18 . Zuo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the composite MAO coatings obtained in the electrolytes containing various nanoparticles have got more attention as they present compactness, microstructure modification, and/or sealing of pores, which leads to better corrosion protection. [15][16][17][18] Zuo et al…”
Section: Introductionmentioning
confidence: 99%